The Readiness of TVET Lecturers in Facing the Intelligence Age IR4.0 - Zulnaidi, Hutkemri; Abdul Rahim, Suzieleez Syrene; Mohd Salleh, Umi Kalsum (Journal of Technical Education and Training, 2020)
Understanding of the industrial revolution 4.0 (IR4.0) and professional ethics are required for lecturers to cope with the intelligence era. However, some lecturers still have poor professional ethics or do not even understand such principles. These two factors have become barriers to the country’s efforts to embrace IR4.0. Thus, this study aims to determine the influence of professional identity and ethics on the readiness of TVET lecturers in facing IR4.0. Data were collected using a combination of two instruments to measure professional ethics, IR4.0 understanding and IR4.0 readiness. A total of 203 technical and vocational education and trainings (TVET) lecturers in Malaysia were chosen for this study by using the simple random sampling method. The findings reveal the significant influence of lecturers’ understanding of the intelligence age and their readiness to face IR4.0. However, professional ethics is not found to be a mediator of the relationship between IR4.0 understanding and readiness. Thus, the Ministry should improve the lecturers’ IR4.0 readiness by providing IR4.0 courses and trainings for lecturers, as well as providing state-of-the-art facilities for teaching and learning technology.